FUNGSI LURAH DALAM MEMBINA PENETAPAN JABATAN RT/RW DI KELURAHAN KOTA BARU PEKANBARU KOTA - Dini Annisa Tifany; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to determined and analyze the performance of the functions of the HeadOffice of assignment in fostering RT/RW in political district administered by a village chief KotaBaru subdistrict Pekanbaru Kota and for to find out the factors that inhibit the function of the HeadOffice of assignment in fostering RT/RW in political district administered by a village chief KotaBaru subdistrict Pekanbaru Kota.This research method using qualitative and quantitative methods. This type of reseacrh thatwill be used is survey research. The sample withdrawal tecnique used in this study the author thereare technique for the population census, head of authors use census given limited population, as wellas the withdrawal of sample RT and RW that is in the location of research using census technique.These result indicate that the functions of the Head Office of assignment in fostering RT/RWin political district administered by a village chief Kota Baru subdistrict Pekanbaru Kota for a goodresponse to the complainant as 6 person or 24% of the respondents. Then for a response less welladdresed as much as 4 person or 16% of the respondents.Keywords: Functions, Head Office of assignment